EFFECT OF LEAD NITRATE ON CARBOHYDRATES AND LIPIDS CONTENT OF CHICKPEA DURING GERMINATION - PIYUSH KUMAR MISHRA (The Journal of Research ANGRAU, 2024)
This study has been carried out to examine effects of lead nitrate on the carbohydrates and fats content of Cicer arietinum L. during germination. This study reported the carbohydrate content in seedling during germination decreased over time. At lead nitrate concentrations of 0 %, 0.025 %, 0.05 %, 0.1 % the carbohydrate concentration increased by 21.6 %, 19.5 %, 15.8 % and 19.5 %, respectively. It was found that the increase in lead nitrate concentration affects the fat content of cotyledon with increasing time period but decreased with the simultaneous rise in lead nitrate concentration. Fat content was 5.3% after 24 h treatment of 0.1% lead nitrate which reduced to 3.5% after 144 h of lead nitrate treatment at the same concentration. Lead nitrate was responsible for the depletion in the synthesis of carbohydrates and fats in seedlings.